TACIT CHOICE OF LAW IN INTERNATIONAL COMMERCIAL CONTRACTS: PROGRESS OR STAGNATION IN THE COMMON- LAW JURISDICTIONS? - Bouwers, Garth J (Obiter, 2023)
The English common-law rules of private international law have, to a large extent, been replaced by European conflicts-law regulations in the United Kingdom (UK). Nevertheless, English common law remains highly influential in numerous jurisdictions. In many legal systems, the private-international-law rules are based fundamentally on the common-law rules developed by English courts. This is problematic since the common-law rules of private international law may be outdated. This article examines the English common-law choice-of-law rules – more specifically, the rules and principles concerning the determination of a tacit choice of law in international commercial contracts. The traditional common-law position is compared to selected common-law jurisdictions – namely, Australia, Canada, India, Israel and New Zealand. Finally, the article highlights the progress (or lack thereof) in the aforementioned common-law jurisdictions in addressing the issues related to the determination of a tacit choice of law in international commercial contracts.